2018
DOI: 10.1080/01446193.2018.1473619
|View full text |Cite
|
Sign up to set email alerts
|

Looking out to look in: inspiration from social sciences for construction management research

Abstract: In reaction to the recent call for critical debate in the field of construction management research, I argue that we should embrace the richness of adjacent fields of study in order to dynamically develop our own and face the plethora of contemporary societal challenges that exist in our industry. I introduce the concepts of other-than-rational thinking in decision-making and multiplicity in management responses as examples of inspirational sources from social sciences that would contribute to truly understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…Turning to the three articles of the special issue, they are further contributions to strands within CM that adopt social scientific approaches (including names such as Bresnen 2017, Davies and Harty 2013, Whyte 2011. They also demonstrate the typical strengths of CM research as having strong connections to practice (Volker 2019).…”
Section: The Three Contributionsmentioning
confidence: 94%
“…Turning to the three articles of the special issue, they are further contributions to strands within CM that adopt social scientific approaches (including names such as Bresnen 2017, Davies and Harty 2013, Whyte 2011. They also demonstrate the typical strengths of CM research as having strong connections to practice (Volker 2019).…”
Section: The Three Contributionsmentioning
confidence: 94%
“…The purpose here was to explore inter-organizational communication in multinational infrastructure projects and to contribute to the development of collaborative models in construction project management. By applying a linguistic perspective on collaboration and communication in multi-cultural and multi-lingual construction project settings, we answered the call from Koch et al [27] and Volker [28] for more interdisciplinary research in construction management. We found that having language competence and the capacity to communicate is not enough to communicate and collaborate in construction projects.…”
Section: Contextual Communicative Competencementioning
confidence: 97%
“…Although there are recent studies regarding multidisciplinary teams in construction (e.g., [22]), communication in construction (e.g., [23]), and new roles in construction (e.g., [24,25]), there seems to be a need for more studies on inter-organizational communication challenges and competence needs in a multinational project context, like that of the STA and its international contractors. Given the call from Koch et al [26] and Volker [27] for more interdisciplinary research in construction management, and by exploring empirical data from contemporary construction projects through theories on relational contracting, language use, and culture, we contribute to bridging a gap in the construction management literature.…”
Section: Introductionmentioning
confidence: 99%
“…His findings point to that impact and cross-fertilisation is low and the need for better engagement both ways if we are to move our understanding of this highly complex sector forward in relevant and meaningful ways. A similar argument is made by Volker (2019), who tackled the issue of the ways in which insights from adjacent fields might inform debates within our own and made compelling arguments for looking beyond the confines of the field in order to diversify and challenge our own thinking. We believe that these are important intellectual debates that have profound impacts on the evolution of our field.…”
Section: Editorialmentioning
confidence: 74%